Comparison of Two Typical Professional Programs for Mechanical Analysis of Interlayer Bonding of Asphalt Pavement Structure - Shuangxi Li; Liang Tang; Kang Yao (Advances in Materials Science and Engineering)
The mechanical analysis of interlayer bonding problem of asphalt pavement is performed by the elastic layered system theory or finite element method (FEM); then, a lot of specialized programs based on the above theories emerged successively, of which BISAR3.0 and EverStressFE are quite representative. In order to further clarify the characteristics of BISAR3.0 and EverStressFE for investigating interlayer bonding problem of asphalt pavement, this paper will carry out a comprehensive comparison from the specific realization viewpoint, such as the principle of interlayer bonding, modeling, calculation processing, and result treatment, and a specific example will be given to compare and analyze their functions. The results indicate that the two programs have certain comparability in analyzing the interlayer bonding problem of asphalt pavement, which will contribute to the foundation for the rational selection of asphalt pavement structure mechanical analysis program.